Association between the mid-upper arm circumference (MUAC) and calf circumference (CC) screening indicators of sarcopenia with the risk of pneumonia in stable patients diagnosed with schizophrenia - Ren, Silan; Huang, Sha; Chen, Ming; Zhu, Tian; Li, Qiuxia; Chen, Xiaoyan (Frontiers in Psychiatry, 2022)
Aim Here, we investigate the relationship between mid-upper arm circumference (MUAC) and calf circumference (CC) screening indicators of sarcopenia and the risk of pneumonia in stable patients diagnosed with schizophrenia. Method The study is prospective and includes inpatients with schizophrenia from two mental health centers in Western China. The studied screening indicators, MUAC and CC were assessed in standing patients. The relationship between MUAC and CC as sarcopenia screening indicators with the risk of pneumonia in patients with schizophrenia was analyzed by performing a statistical logistic regression analysis. Result For this study, 339 patients with schizophrenia, aged 50 years and over were recruited. Moreover, four patients with pneumonia that occurred within 1 week of the relapse of schizophrenia were excluded. As a result, only 335 patients were included in the analysis. Pneumonia has been reported in 82 (24.5%) of all included patients with schizophrenia. Our data analysis confirmed that in the male patients, the higher CC was associated with a lower risk of pneumonia (odds ratio [OR] = 0.751, 95% CI: 0.635–0.889). We have divided men into two cohorts following the values of CC. Our analysis further showed that the patients with CC ≥ 34 cm had a lower risk of pneumonia in men (OR = 0.36, 95% CI: 0.163–0.795). Conclusion We demonstrate that CC is associated with pneumonia risk in stable men with schizophrenia.